Penerapan Model Pembelajaran Picture and picture dalam Pembelajaran Menulis Teks Fabel Siswa Kelas VII SMPN 1 Sungai Lala - Adelia, Riska; Auzar, Auzar; Permatasari, Silvia (Universitas Negeri Padang, 2024)
Students' ability to write fable text can be categorized as low. The conventional learning model is one of the causes of students' difficulties in writing fable texts. Student's difficulties in writing fable texts and the lack of teaching materials are some problems highlighted in interviews conducted with Indonesian language teachers at SMPN 1 Sungai Lala. Therefore, the researcher applied Picture and picture learning methodology as an alternative to overcome the problems experienced by students. Thus, this study assessed how well the Picture and picture model can improve students' ability to write fable prose. The sample in this study was 63 students in class VIII of SMPN 1 Sungai Lala. This study used a quasi-experimental approach, where the study compared two groups: the group that used the picture and picture paradigm and the group that used the standard model. The findings showed that the experimental group's writing ability improved significantly, and there was a notable difference between the two groups. Thus, the researcher can conclude that the Picture and picture model can improve the ability to write fable texts at SMPN 1 Sungai Lala, especially for class VIII.